2000
DOI: 10.1007/s004320050028
|View full text |Cite
|
Sign up to set email alerts
|

Nephrotoxicity of ifosfamide, carboplatin and etoposide (ICE) alone or combined with extracorporeal or radiant-heat-induced whole-body hyperthermia

Abstract: Although whole-body hyperthermia combined with specific genotoxic chemotherapy can be shown to enhance neoplastic cell killing without a concomitant rise in bone marrow toxicity, nephrotoxicity can become treatment-limiting. This study compares the kidney toxicity to the kidney of ifosfamide, carboplatin and etoposide (ICE) chemotherapy alone, and ICE chemotherapy combined with either extracorporeal (e-WBH) or radiant-heat-induced hyperthermia (r-WBH) in 43 patients with refractory sarcoma. Within 3 days of IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Renal damage is the major non-hematological toxicity. Gerke et al [16] showed both transient and long-term increase in urinary protein excretion and a reduction of glomerular filtration rate in patients receiving ICE regime alone or in combination with extracorporeal whole-body hyperthermia. Fanconi renal tubular dysfunction with glycosuria, proteinuria, hypokalemia, and hyophosphatemia was reported by Kung et al [17] in 6 out of 21 patients with recurrent Wilms tumor treated with ICE.…”
Section: Discussionmentioning
confidence: 99%
“…Renal damage is the major non-hematological toxicity. Gerke et al [16] showed both transient and long-term increase in urinary protein excretion and a reduction of glomerular filtration rate in patients receiving ICE regime alone or in combination with extracorporeal whole-body hyperthermia. Fanconi renal tubular dysfunction with glycosuria, proteinuria, hypokalemia, and hyophosphatemia was reported by Kung et al [17] in 6 out of 21 patients with recurrent Wilms tumor treated with ICE.…”
Section: Discussionmentioning
confidence: 99%
“…WBH can be combined with chemotherapy to increase tumor cell death without increasing bone marrow suppression. 122 A newer approach is to increase the temperature to ~ 40°C for a longer period, which, in combination with cytokines and cytotoxic drugs, is expected to lead to a greater therapeutic index than WBH at the maximum tolerated level. 123 WBH can be applied only to patients in a good health.…”
Section: Whole-body Hyperthermia (Wbh)mentioning
confidence: 99%
“…Median OS, from begin of treatment: 50 weeks (95% CI: 39–61 weeks) 3. 46% According to WHO (n = 44) Related to WBH: Mucosal herpes infections: n = 17, responsive to acyclovir Pressure scores (grade 1 and 2): n = 3 Transient cardiac arrhythmias with ECG signs of myocardial ischaemia (grade 3): n = 5 Comparison Group A and B: Haematological toxicity : In cycles with WBH: grade 0: 91.7%, grade 1: 2.6%, grade 2: 4.4%, grade 3: 1.2% In cycles without WBH: grade 0: 93.7%, grade 1: 1.6%, grade 2: 2.8%, grade 3: 1.9% Gastrointestinal toxicity : In cycles with WBH: grade 0: 82.6%, grade 1: 11%, grade 2: 4.9%, grade 3: 1.5% In cycles without WBH: grade 0: 85.5%, grade 1: 9.6%, grade 2: 3.7%, grade 3: 1.2% Peripheral neurotoxicity : In cycle with WBH: grade 0: 39.2%, grade 1: 40.8%, grade 2: 18.5%, grade 3: 1.5% In cycle without WBH: grade 0: 49.0%, grade 1: 35.0%, grade 2: 14.7%, grade 3: 1.4% Fatigue syndrome : In cycle with WBH: grade 3: 20%, grade 4: 5% In cycle without WBH: grade 3: 6%, grade 4: 3% Related to Oxaliplatin: Most frequent: mild neurosensory toxicities: 68% Severe sensory neuropathy with functional impairment due to loss of sensitivity in fingertips and soles of feet towards end of therapy: n = 1 Almost all patients reported neurotoxicity to be less pronounced in cycles combined with WBH Gerke et al [ 49 ] Arm A : ECC-WBH (Level One) + CTx (n = 9) Arm B: rWBH (Aquatherm) + CTx (n = 18) Arm C: CTx alone (n = 16) Type of cancer: Sarcoma Duration target temp. per session: 41.8 °C for 1 h Number of treatments: 4–6 courses Period of time: January–December 1995 1.…”
Section: Resultsmentioning
confidence: 99%